Pelatihan Penggunaan Platform Merdeka Mengajar Bagi Guru-Guru SD Korwil II Bengkulu Utara - Dhanu Ario Putra; Merry Rullyanti; Eli Diana; Jezen Bernando; Selidia Tuastia (Universitas Dehasen Bengkulu, 2023)
Merdeka Mengajar Platform is a tech advance which help teachers in teaching, learning and working. Teachers can obtain references, inspirations and understandings in implementing Merdeka Mengajar program. This application is very useful for driving force teachers. In reality, many teachers who still haven’t able to use or even access the application even tough they already have the ID (Special ID for teachers). The purpose of this devotion is to socialize and train elementary school teachers at regional coordinator I how to use the application and the understanding of P5 Pancasila. The method which is used in this devotion is face to face and presentation. The target of the devotion is teachers in Sub-Division I of North Bengkulu. The program conducted at SDN 116 of North Bengkulu. After the devotion, the teachers understand and know how the benefit of Merdeka Mengajar Application and feel the benefit of P5 Pancasila.